Exactly solved model for an electronic Mach-Zehnder interferometer - Kovrizhin, D; Chalker, J (American Physical Society, 2009)
We study nonequilibrium properties of an electronic Mach-Zehnder interferometer built from integer quantum Hall edge states at filling fraction ν=1. For a model in which electrons interact only when they are inside the interferometer, we calculate exactly the visibility and phase of Aharonov-Bohm fringes at finite source-drain bias. When interactions are strong, we show that a lobe structure develops in visibility as a function of bias, while the phase of fringes is independent of bias, except near zeros of visibility. Both features match the results of recent experiments [Neder et al., Phys. Rev. Lett. 96, 016804 (2006)].